Revitalizing Sundanese Pupujian: A Socio-Religious, Linguistic, and Cultural Transmission Analysis in Eight Regions of West Java - Amanat, Tri; Fahmi, Royan Nur; Zaman, Saefu (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The Sundanese pupujian tradition represents a vital form of oral liturgical poetry chanted in mosques and madrasas across West Java. This study documents this endangered cultural heritage across eight distinct regions: Bogor, Sukabumi, Purwakarta, Tasikmalaya, Ciamis, Majalengka, Indramayu, and Cirebon. Driven by modern urban dynamics, this tradition faces rapid decline. Utilizing a qualitative methodology integrating fieldwork interviews, historical tracing, and linguistic analysis, this paper dissects the socio-religious dimensions of pupujian. Findings reveal rich thematic content divided into theology (tauhid), prophetic praise (sholawat), eschatology, and Islamic didacticism. Linguistically, the tradition showcases localized dialectal variations synthesized with traditional Sundanese pentatonic scales (pélog and saléndro). This structures a regional accentuation while maintaining a historically consistent core message originating from the early Islamization era of West Java.